Present and future of extraoral maxillofacial prosthodontics: Cancer rehabilitation - Salazar-Gamarra, Rodrigo; Binasco, Salvatore; Seelaus, Rosemary; Dib, Luciando Lauria (Frontiers in Oral Health, 2022)
There has been evidence since the recorded time of people's desire to overcome facial differences. Our history includes multiple efforts in materials, methods, and artisanal techniques. Nowadays, extraoral maxillofacial rehabilitation of the present time is managed by a multi-professional team that has built a broadening knowledge, skills, and responsibility. These include a mandatory integration of different professionals that can cover the bio-psycho-social needs of the patient, systemic health and pathology surveillance, and advanced restorative techniques, which may include 3D technologies. In addition, recent digital workflows allow us to optimize this multidisciplinary integration and reduce the active time of both patients and clinicians, as well as the cost-efficiency of the care system, promoting its access to both patients and health systems. This paper discusses factors that affect extraoral maxillofacial rehabilitation's present and future opportunities from teamwork consolidation, techniques, and health systems opportunities.